CYP17A1 rs743572 polymorphism might contribute to endometriosis susceptibility: evidences from a case–control study - Cong, Lili (Medicine (Baltimore), 2018)
This case–control study was aimed to evaluate the influence of cytochrome P450 family 17 subfamily A member 1 (CYP17A1) gene rs743572 polymorphism for the susceptibility to endometriosis. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used to genotype rs743572 polymorphism in 143 endometriosis patients and 148 healthy controls. Hardy–Weinberg equilibrium (HWE) test was utilized to detect the representativeness of the study subjects. Association strength was presented by odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Genotype distribution of rs743572 polymorphism was conformed to HWE test both in case and control groups, revealing the good representativeness of our study subjects. Significantly positive association was discovered between rs743572 TT genotype and endometriosis susceptibility (P = .042, OR = 1.952, 95% CI = 1.020–3.736). Rs743572 T allele was more frequently discovered in cases than that in controls, revealing the enhanced susceptibility to endometriosis (P = .041, OR = 1.407, 95% CI = 1.014–1.951). Confounding factors (age and body mass index) were utilized to adjust the results, and then we found that the association strength had no significant changes (TT vs CC, P = .039, OR = 1.961, 95% CI = 1.023–3.742; T vs C, P = .038, OR = 1.413, 95% CI = 1.016–1.957). But we failed to find any obvious association of rs743572 genotypes with endometriosis stages and characteristics. T allele of rs743572 polymorphism might act as a risk factor for endometriosis, although it had no effects on the disease stages and basic features.